The double dividend issue: Modeling strategies and empirical findings - Francesco Bosello; Carlo Carraro; Marzio Galeotti (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper reviews recent developments in the study of the so-called "double dividend", i.e. the possibility of improving the environment and, at the same time, reducing the distortions of the tax system through revenue-neutral green taxes. Recent modeling advances are considered at both the theoretical and the empirical levels. In particular, we note that the most significant theoretical advances have been made in the direction of allowing for imperfectly competitive markets, especially the market for labor. At the same time, we argue that empirical work, particularly on the "employment double dividend", is still relatively scant and that much more needs to be done both in the direction of more realistic empirical models and of an extended sensitivity analysis of the main findings.
Keywords: H0; H2; H3; 330; Double dividend; Environmental fiscal reform; Environmental modeling; Ökosteuer; Beschäftigung; Öffentliche Einnahmen; Empirische Methode; Theorie